Primary breast angiosarcoma in postmenopausal women with a picture like Kasabach-Merritt syndrome: A case report - Ćuk Mirjana; Gajanin Radoslav; Marić Radmil; Marić Veljko; Todorović Svjetlana; Vasić-Milanović Milena (Vojnosanitetski Pregled)
Introduction. Primary breast angiosarcoma is a very rare tumor and accounts for 0.04% of all breast malignant tumors and most commonly occur in young women. Kasabach-Merritt syndrome (KMS) is described as consumption coagulopathy with thrombocytopenia, and without adequate therapy almost certainly leads to a very fast lethal outcome. Case report. We present a rare case of 60-year-old postmenopausal woman with metastatic primary angiosarcoma of the breast associated with a picture like Kasabach-Merritt's syndrome (thrombocytopenia and anemia without the coagulation factor disorder with massive bleeding in the tumor). Conclusion. Primary breast angiosarcoma in postmenopausal women is a very rare tumor, and may be associated with anemia and thrombocytopenia without other laboratory parameters for Kasabach-Merritt's syndrome. Anemia and thrombocytopenia are refractory to standard treatment protocols, and also significantly reduces the quality of life of these patients. The literature contains only a few cases of Passociated with thrombocytopenia or with KMS and there are no clear defined protocols for the treatment of these patients, which requires the presentation of as many cases as possible.